2020
DOI: 10.21203/rs.3.rs-31172/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and validation of a survival model based on autophagy-associated genes for predicting prognosis of hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the devastating tumors with increasing incidence. Autophagy-associated genes (ARGs) are widely participated in the cellular processes of HCC. This study proposed to identify the novel prognostic gene signature based on ARGs in HCC. Methods: We downloaded the RNA sequencing data and clinical information of HCC and normal tissues from The Cancer Genome Atlas (TCGA) database. The differentially expressed ARGs were screened by the Wilcoxon signed-rank test. Func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…p62 (also known as sequestosome 1) is a multifunctional adapter protein that is involved in various physiological functions (29), including nuclear factor-ĸB signaling (30)(31)(32)(33), antioxidant response (34) and autophagy (35)(36)(37). p62 is overexpressed (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) in several cancer types, and high p62 expression is associated with poor prognosis (41,44,46,(49)(50)(51)(52) in several types of cancer. In breast cancer, p62 gene and protein are overexpressed (53)(54)(55) and high p62 protein expression is associated with poor prognosis of overall and disease-free survival (54,56).…”
mentioning
confidence: 99%
“…p62 (also known as sequestosome 1) is a multifunctional adapter protein that is involved in various physiological functions (29), including nuclear factor-ĸB signaling (30)(31)(32)(33), antioxidant response (34) and autophagy (35)(36)(37). p62 is overexpressed (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) in several cancer types, and high p62 expression is associated with poor prognosis (41,44,46,(49)(50)(51)(52) in several types of cancer. In breast cancer, p62 gene and protein are overexpressed (53)(54)(55) and high p62 protein expression is associated with poor prognosis of overall and disease-free survival (54,56).…”
mentioning
confidence: 99%
“…BIRC5 expression could reflect aggressive histological and clinical behavior of HCC, correlating with poorer OS (Kapiris et al, 2019). Present studies have shown that BIRC5 is closely related with autophagy, and several survival indexes containing BIRC5 were proved to have promising predictive value (Yang et al, 2020;Qin et al, 2021;Wang et al, 2021). Jiao et al once reported that YAP promoted sorafenib resistance in HCC by upregulating BIRC5 (Sun et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“… 12 In the meanwhile, several studies also constructed prognostic signatures for HCC overall survival prediction based on autophagy-associated genes. 13 , 14 These prognostic models could serve as predictor for survival and play key roles in tumor microenvironment. In order to identify potential biomarkers, we used the TCGA database to analyze differences in immunoautophagy-related gene expression between HCC and normal tissues in our study.…”
Section: Discussionmentioning
confidence: 99%
“…10 Thus, the combination of autophagy and immunotherapy may provide us with a promising strategy for tumor treatment, requires further study. However, few previous studies have established some prognosis model of HCC based on immune-related genes 11,12 or autophagy-related genes, 13,14 but no studies have explored the relationship between immunoautophagy-related genes and investigate its prognosis of HCC. With the currently available autophagy-related genes (ARGs) and immune-related genes (IRGs), and the accumulative data deposited in public databases, it is hypothesized that a prognostic signature based on the immune response and autophagy might help to identify HCC patients' survival profile.…”
Section: Introductionmentioning
confidence: 99%